In Search for Anchors The Fundamental Motivational Force in Compensating for Human Vulnerability - Riyono, Bagus; Himam, Fathul; -, Subandi (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2012)
The purpose of this study is to develop a new integrative theory of motivation drawn from the existing theories and data. The method used is a combination of meta-ethnography and grounded theory. The second phase of the study employed a thought experiment to test the newly developed theoretical propositions of motivational force. The first phase of the study revealed a central phenomenon for the occurrence of motivational force, i.e. âIn Search for Anchors,â which is a result of the paradox between freedom to choose and human vulnerability. âFreedom to chooseâ is the central factor of a motivational model that includes âurge,â âchallenge,â âincentive,â and âmeaning.â These five factors are motivational sources, which have holistic-dynamic-integrative interaction. Human vulnerability is the other side of the motivational model that comprises risk, uncertainty, and hope that ignite motivational force. The dynamic interaction of risk, uncertainty, and hope is represented in a mathematical formula that produces the strength of the force, (R â H)2 x U, which can be potrayed in a âtwin-peakâ curve. The thought experiment was conducted to test the hypothetical formula. The result shows that the âtwin-peakâ hypothesis is supported but the shape of the curve is found to be not symmetrical. The data show that hope is the strongest motivational force, therefore the formula is modified into = (R â U)2 x H. The implication of the study and the utility of the new theory are discussed.Â Â Â Â Â Â Â Â